Some method on survival analysis via Weibull model in the present of partly interval censored: a short review - Fauzi , Nurul Akma; Elfaki, Faiz Ahmed Mohamed; Yeakub Ali , Mohammad (IJCSNS, 2015)
Survival analysis or known as failure time analysis has its own achievement in the medical application. Thus, a few of researcher found that it also can be applied in the engineering application as it is one of the robust methods in the data analysis. Partly interval censoring is one of the censoring techniques that used in the survival analysis and it is developed by using Weibull distribution model. Weibull distribution model is one of the analysis techniques that commonly used as a lifetime distribution in the reliability applications. Thus, the estimation of parameter is needed in order to increase the flexibility of Weibull distribution so that it can suit in any condition of the treated data in engineering applications.